2017
DOI: 10.1093/botlinnean/box031
|View full text |Cite
|
Sign up to set email alerts
|

Macroclimatic niche limits and the evolution of C4 photosynthesis in Gomphrenoideae (Amaranthaceae)

Abstract: During the evolution of vascular plants, C 4 photosynthesis has developed > 60 times, but most studies concerning the evolution and the ecophysiological advantages of the C 4 syndrome have been carried out in grasses. Among eudicots, C 4 photosynthesis has developed in lineages that are morphologically more diverse than the relatively homogeneous grasses, and conclusions about C 4 evolution based on grasses may or may not apply to eudicots. Little is known about the origin of C 4 photosynthesis in Amaranthacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
(71 reference statements)
1
6
0
2
Order By: Relevance
“…(2007) only included five Gomphrena species to map the evolution of C 4 photosynthesis on the tree of Amaranthaceae and revealed a common origin of C 4 in species of Gomphrena belonging to "clade a" alongside with Philoxerus, Guilleminea and Froelichia. This result was confirmed by Bena & al. (2017) who tested if the evolution of the C 4 pathway correlated with changes in macroclimatic niches and found that C 4 Gomphrenoideae specialized to dryer regions compared to their C 3 relatives and then expanded into colder environments.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…(2007) only included five Gomphrena species to map the evolution of C 4 photosynthesis on the tree of Amaranthaceae and revealed a common origin of C 4 in species of Gomphrena belonging to "clade a" alongside with Philoxerus, Guilleminea and Froelichia. This result was confirmed by Bena & al. (2017) who tested if the evolution of the C 4 pathway correlated with changes in macroclimatic niches and found that C 4 Gomphrenoideae specialized to dryer regions compared to their C 3 relatives and then expanded into colder environments.…”
Section: Introductionsupporting
confidence: 88%
“…(2009), Sage & al. (2007) and Bena & al. (2017) show that the gomphrenoid clade contains species of Gomphrena in two different lineages: The first lineage comprises Lithophila, Gossypianthus and Philoxerus (= Blutaparon) along with most species of Gomphrena (= Gomphrena s.str.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…; Bena et al . ). However, our analysis is the first to show that C 4 photosynthesis also increased the rate of transitions among climate types, with frequent migration into temperate climates without freezing (Fig.…”
Section: Discussionmentioning
confidence: 97%